CONTRIBUTIVE EFFECT OF LOCAL GOVERNMENT REVENUE ON ECONOMIC DEVELOPMENT IN NIGERIA (Journal of Contemporary Issues in Accounting, 2024)
This study concisely examined the contributive effect of Local Government revenue on economic Development in Nigeria. Specifically, the study examines how much local government revenue from Federation Account (FAAC), State allocation, Internally Generated Revenue, Value Added Tax (VAT), Grants and others have affected the Real Gross Domestic Product (RGDP) in Nigeria using time series data from 1993 – 2022. The data was analysed using the traditional OLS technique, Diagnostic test and Granger causality test were carried out on the data obtained from the Central Bank of Nigeria. The study in order to prevent occurrence of correlation of variables equally carried out the serial correlation LM test which clearly indicates that there was no correlation between the variables in the model. This is because  the p-value are insignificant at 5% level of significance. The findings show that local government revenue from the various sources as contained in the study significantly affects economic development in Nigeria. Unidirectional link runs between Value Added Tax of local government revenue to real GDP in Nigeria. The study recommends among other things that local governments should be granted financial autonomy with periodic value for money audit as this will minimize wastage and maximize fiscal responsibility towards utilizing local government revenue for infrastructural and economic development in Nigeria.
Keywords: Economic Development; Federal Allocation; Internally Generated Revenue; Local Government; Revenue; State Allocation